Vegetation composition, soil properties, and carbon stock of montane forests along a disturbance in the Garhwal Himalaya, India - Tiwari, Avadhesh; Khanduri, Vinod Prasad; Rawat, Deepa; Singh, Bhupendra; Riyal, Manoj Kumar; Mishra, Gaurav; Kumar, Munesh (Frontiers in Forests and Global Change, 2023)
The management of forests is essential for the conservation of biodiversity and climate change. The studies on variation in forest tree diversity and carbon sequestration by the forests along altitudinal gradients are limited in the most parts of Garhwal Himalaya. The present study was carried out in Montane forests in a part of district Tehri of Garhwal Himalaya, India at four different sites between altitudinal ranges of 850 to 2200 m asl (i.e., 850-1500 m asl under sub-tropical region and 1800-2200 m asl under temperate region) for vegetation, soil, and carbon stock analysis using different parameters including existing pressure on the sites for fuel, fodder, timber, grazing, browsing etc.. All the standard methods were used for vegetation and soil analysis. The highest value of tree diversity (H=0.48) and concentration of dominance (CD= 0.95) was recorded at 850-1100 m asl altitude under sub-tropical forests. The above ground biomass density (AGBD) and below ground biomass density (BGBD) ranged from 271 to 703.20 and 83.21 to 163.92 Mg ha-1 respectively. The pH value ranged from 5.63-6.86 (0-15 cm) and 6.17- 7.21 (15-30 cm). Similarly, soil organic carbon (SOC) was reported to be ranging between1.86 to 2.57 and 1.78-2.44% at 0-15cm and 15-30 cm depths, respectively. Available nitrogen (N) under temperate forests was reported significantly higher than at other altitudes. Among the studied parameters, a significant positive correlation was reported between the pH of the soil and with Shannon-Wiener and Margalef diversity index. The study revealed that the sub-tropical region was more diversified in terms of tree species whereas; soil properties reported better in the temperate region. Among the species of the study region, Pinus roxburghii, Boswellia serrata, Quercus leucotrichophora and Cedrus deodara have shown good potential for carbon storage. Thus, based on the dominance and associated species present in the area, forest management activities may be followed for the survival and regeneration of species, having the potential of being the next dominant species in future of succession history.